Nucleoside Diphosphate-sugar 4-Epimerases I. Uridine Diphosphate Glucose 4-Epimerase of Wheat Germ - Fan, Der-Fong (1969)
Uridine diphosphate (UDP)-glucose 4-epimerase (EC 5.1.3.2) has been purified over 1000-fold from extracts of wheat germ by MnCl(2) treatment, (NH(4))(2)SO(4) fractionation, Sephadex column chromatography, and adsorption onto and elution from calcium phosphate gel. The enzyme has a pH optimum of 9.0. Km values are 0.1 mm for UDP-d-galactose and 0.2 mm for UDP-d-glucose. NAD is required for activity; K(a) = 0.04 mm. NADH is an inhibitor strictly competitive with NAD; K(i) = 2 μm. Wheat germ also contains UDP-l-arabinose 4-epimerase (EC 5.1.3.5) and thymidine diphosphate (TDP)-glucose 4-epimerase which are distinct from UDP-glucose 4-epimerase.